Implementation of Deep Learning Curriculum in STEM Education: A Case Study in Secondary Schools in Bengkulu - Nofirman (Lembaga KITA, 2025)
Background Holistic STEM (science, technology, engineering, and mathematics) education is essential to harness the potential of young learners as they are the future leaders and workforce in the Industrial Revolution (IR) 4.0 and Society 5.0 era. Unfortunately, the teaching of STEM subjects that are rich in content does not necessarily encourage the development of talents for critical thinking, creativity, and complex problem solving. This study investigates the effectiveness of an immersive learning approach in STEM science classes in Senior High Schools in Indonesia and explains the extent to which this approach is supported by applicable principles on how this approach can be used to enhance student learning. Referring to a case study conducted in a senior high school in Bengkulu, this study discusses the strategies implemented, the challenges faced, and their impact on student engagement and understanding of content and learning 21st century skills. The findings indicate that the integrated immersive learning STEM curriculum in schools has resulted in an 82.5% increase in student learning motivation, a 20% 35% increase in programming skills, and a 27.5% increase in collaboration skills. However, obstacles such as teacher education and technological facility constraints still exist. Based on various perspectives and real-world experiences, this note recommends a critical approach to promote the embedding of deep learning in STEM education through targeted policies and systemic support. Hopefully, these suggestions can build educational innovations that are sustainable enough to be disseminated to other regions in Indonesia.